Effect of ultrasonic power and frequency on rheological properties of Chinese honey. (February 2021) - Jiang, Mengmeng; Zhu, Wenxue; Ruan, Shulan; Jia, Yanjie; Bai, Xiting; Sun, Jun
Abstract: This study investigates the mechanism and effect of ultrasonic technology on viscous materials such as honey. The rheological properties, viscosity and temperature correlation models, thermodynamic characteristics, main saccharide composition and intramolecular structure of honey samples treated with different ultrasonic powers and frequencies have been investigated. The results showed that the selected ultrasonic combination of conditions did not change the Newtonian fluid characteristics of honey, but the heat effect of ultrasound reduced the moisture content of honey. The Willian–Landel–Ferry (WLF) equation appeared to be more accurate than Arrhenius equation ( R 2 > 0.97) to describe the correlation between viscosity and temperature of honey with high ultrasonic power (>80 W) and low moisture content below 17.1% ( R 2 > 0.98). The differential scanning calorimetric (DSC) experiments showed that the Tg value of honey was significantly decreased by ultrasound ( P < 0.05), which was proportional to the degree of ultrasonic damage. Major saccharides (fructose, glucose, sucrose and maltose) of honey have been greatly affected by high ultrasonic power. The infrared spectroscopy experiment indicated that, under the same ultrasonic power, 40 kHz frequency has significantly increased the wavenumber and number of the absorption peaks of the groups in honey molecules than 28 kHz. Highlights: The effect of ultrasonic power and frequency on honey rheological properties was assessed. The impact of high-power ultrasound on the content of honey components was significant. The molecular structure of honey damaged by the 40 kHz ultrasonic frequency was larger than that of the 28 kHz ultrasonic frequency.